AQUEOUS BARK EXTRACT OF TERMINALIA ARJUNA PROTECTS AGAINST PHENYLHYDRAZINE INDUCED OXIDATIVE DAMAGE IN GOAT RED BLOOD CELL MEMBRANE BOUND AND METABOLIC ENZYMES - Paul, Sudeshna; Ghosh, Debosree; Ghosh, Arnab Kumar; Bhowmick, Debajit; Bandyopadhyay, Debasish; Chattopadhyay, Aindrila (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the present study is to determine the phenylhydrazine (PHZ) induced oxidative stress mediated alteration in the metabolic status and morphology of the red blood cells (RBC) and amelioration of the same by aqueous bark extract of Terminalia arjuna (TA). Methods: Fresh goat blood collected from local Kolkata Corporation approved slaughter house, was used for the present study. Packed cells were prepared from the freshly collected goat blood and were divided into four groups as follows for further studies i. e Group I: Control (CON), Group II: TA bark extract treated, named T5C (5 mg/ml, incubation mixture; positive control), Group III: PHZ treated (1 mM), Group IV: PHZ treated+TA bark extract at a dose of 5 mg/ml, named as P+T5. ROS, superoxide anion radical, and hydroxyl radical scavenging activity were determined. Intracellular iron and intracellular nitrate concentration were estimated. Activities of various membrane-bound enzymes like Na+/K+-ATPase, Mg2+-ATPase and Ca2+-ATPase and Ach-E were determined. Moreover, the activities of some metabolic enzymes like glucose 6-phosphate dehydrogenase (G6PDH), hexokinase, aldolase, lactase dehydrogenase were also studied. In addition, the morphological structure of RBCs was also determined. Results: PHZ treatment caused significant alterations in RBC morphology as well as altered the activities of membrane-bound as well as metabolic enzymes. All these changes following oxidative stress were found to be ameliorated when the RBCs were co-treated with PHZ and aqueous bark extract of TA. However, aqueous bark extract of TA alone did not exhibit any such changes in RBC. Conclusion: The aqueous bark extract of TA ameliorates PHZ-induced oxidative damages in goat RBC possibly by an antioxidant mechanism(s). The aqueous bark extract of TA may have future therapeutic relevance in oxidative stress-induced damages in RBCs. Keywords: Antioxidant enzymes, Aqueous bark extract, Oxidative stress, Phenylhydrazine, Red blood cells, Terminalia arjuna